Prolonged Bleeding after a Single Leech Application in Pediatric Hand Surgery - Kotick, James D.; Taghinia, Amir (Journal of Hand and Microsurgery, 2017)
Use of the medicinal leech in microsurgery is common place for venous decongestion and can be associated with the need for transfusion over time and multiple applications. Here the authors present a case of profound, ongoing, life-threatening bleeding after a single leech application in pediatric microscopic surgery. There are no reports of such profound bleeding in the literature, and this case serves as a warning of the need for close surveillance in this subset of patients.
Keywords: leech therapy; pediatric hand microsurgery; single leech application